5(x+5)-8=26-3x-9+8x

Simple and best practice solution for 5(x+5)-8=26-3x-9+8x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+5)-8=26-3x-9+8x equation:


Simplifying
5(x + 5) + -8 = 26 + -3x + -9 + 8x

Reorder the terms:
5(5 + x) + -8 = 26 + -3x + -9 + 8x
(5 * 5 + x * 5) + -8 = 26 + -3x + -9 + 8x
(25 + 5x) + -8 = 26 + -3x + -9 + 8x

Reorder the terms:
25 + -8 + 5x = 26 + -3x + -9 + 8x

Combine like terms: 25 + -8 = 17
17 + 5x = 26 + -3x + -9 + 8x

Reorder the terms:
17 + 5x = 26 + -9 + -3x + 8x

Combine like terms: 26 + -9 = 17
17 + 5x = 17 + -3x + 8x

Combine like terms: -3x + 8x = 5x
17 + 5x = 17 + 5x

Add '-17' to each side of the equation.
17 + -17 + 5x = 17 + -17 + 5x

Combine like terms: 17 + -17 = 0
0 + 5x = 17 + -17 + 5x
5x = 17 + -17 + 5x

Combine like terms: 17 + -17 = 0
5x = 0 + 5x
5x = 5x

Add '-5x' to each side of the equation.
5x + -5x = 5x + -5x

Combine like terms: 5x + -5x = 0
0 = 5x + -5x

Combine like terms: 5x + -5x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 5.6a=.8(4-a) | | -2(5k-1)=-6(k+1) | | (3-2m)-(3m-2)= | | 25x+20y=220 | | 5xI+5=45 | | 1.6x=4.75 | | -2b-18+5b=-4 | | 3r-6=2r-2 | | 8(x-2)=12 | | 4(1-5x)+6=-26-8x | | 22-4x= | | 5(1+6n)-8(3n+3)=-67 | | 12r=R+1*8 | | 4(2*2+3)=-3(2-1)+31 | | -6+5(x-3)=14x+4-9x | | .33(9-6m)+.75(12m+8)= | | 10=-(n-5)-3(4n-6) | | -4x+-6=26 | | 3x^2+x^2=360 | | 38-4x=7x-6(6+8x) | | 0.3x-0.5(2x+3)=-0.8(x+2) | | -6x=3-21 | | 29+8v=-8(v-7)+7v | | 2x-x=4x+3 | | 2(2x-3)-2(2-3x)= | | X^2-81=o | | -8(0.1x+0.4)-1.9=-0.3 | | 2y-8=8x | | 3k-2x=t-5 | | -20+4+y=-6+16 | | -1=2p | | 4n-12-7n=6-2n-9 |

Equations solver categories